Collaboration in the design and delivery of a mental health Recovery College course: experiences of students and tutors. (4th July 2018) - Cameron, Josh; Hart, Angie; Brooker, Saff; Neale, Paul; Reardon, Mair
Abstract: Background : Recovery Colleges address mental health challenges using an educative approach underpinned by a collaborative recovery orientated philosophy. Research has been limited with no studies identified reporting research on the design and delivery of a specific course. Aims : To understand how Recovery College students and tutors experience the design and delivery of a mental health Recovery College course, specifically the "'Building Resilience" course. Method : Thematic analysis of qualitative data related to the experience and process of collaboration in recovery college course design and delivery. Data included 13 qualitative individual interviews with course students and tutors and "naturally occurring" data generated through course preparation and delivery. Results : Findings drew attention to the centrality of: prior experience and design related to students, tutors and the course structure; co-delivery related to tutors and co-learner impacts; and to the course methods and environment. Conclusions : Commitment to collaboration in design and delivery of Recovery College courses can mobilise the diverse experiences and expertise of tutors and students. The environment and methods of learning have a significant impact and should be considered alongside content. Boundaries between people and areas of knowledge and experience that arise can be viewed as sources of creativity that can enrich courses.